2015
DOI: 10.1111/jdv.13240
|View full text |Cite
|
Sign up to set email alerts
|

Long pulse Alexandrite laser for recalcitrant viral warts on the hands

Abstract: EditorWarts affecting the hands in particular among other types, are a cause of physical and psychological discomfort to patients. Clearance rate with current therapeutic approaches remains low. A prospective randomised trial reported a clearance rate of 39% with cryotherapy, 24% with SA and 16% in the wait-and-see arm.1 CO 2 laser was shown to be effective in the treatment of recalcitrant periungueal warts. Its cure rate has been shown to be 64% at 12 months. 2 Several studies have reported the efficacy of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Another case series 42 described using the diode laser for facial flat warts in 3 patients and achieved a resolution rate of 100% in 1 patient and nearly complete resolution in 2 patients during a follow-up period of ∼24 months. Other case reports described the use of the long-pulsed alexandrite laser 43 ( n = 1) and potassium titanyl phosphate 44 ( n = 1) achieving a resolution rate of 100% with follow-up periods of 12 and 10 months, respectively. A summary of the results from studies using other lasers can be found in Supplemental Digital Content 1 , Table S4, http://links.lww.com/DSS/B362.…”
Section: Resultsmentioning
confidence: 99%
“…Another case series 42 described using the diode laser for facial flat warts in 3 patients and achieved a resolution rate of 100% in 1 patient and nearly complete resolution in 2 patients during a follow-up period of ∼24 months. Other case reports described the use of the long-pulsed alexandrite laser 43 ( n = 1) and potassium titanyl phosphate 44 ( n = 1) achieving a resolution rate of 100% with follow-up periods of 12 and 10 months, respectively. A summary of the results from studies using other lasers can be found in Supplemental Digital Content 1 , Table S4, http://links.lww.com/DSS/B362.…”
Section: Resultsmentioning
confidence: 99%
“…Not only that, the long-pulse alexandrite laser has also shown potential in the treatment of venous lakes of lips, recalcitrant viral warts, and basal cell nevus syndrome, but systematic studies with larger sample sizes or comparisons with different lasers are still lacking. [36][37][38] This article summarizes the following key aspects that should be considered in the application of long-pulse alexandrite laser treatment. First, reasonable treatment parameters should be selected according to the patient's skin color, lesion depth, and the content of target chromophores in the lesion.…”
Section: Discussionmentioning
confidence: 99%